Patient-specific mutations impair BESTROPHIN1’s essential role in mediating Ca2+-dependent Cl- currents in human RPE - Yao Li; Yu Zhang; Yu Xu; Alec Kittredge; Nancy Ward; Shoudeng Chen; Stephen H Tsang; Tingting Yang (eLife, 2017)
Mutations in the human BEST1 gene lead to retinal degenerative diseases displaying progressive vision loss and even blindness. BESTROPHIN1, encoded by BEST1, is predominantly expressed in retinal pigment epithelium (RPE), but its physiological role has been a mystery for the last two decades. Using a patient-specific iPSC-based disease model and interdisciplinary approaches, we comprehensively analyzed two distinct BEST1 patient mutations, and discovered mechanistic correlations between patient clinical phenotypes, electrophysiology in their RPEs, and the structure and function of BESTROPHIN1 mutant channels. Our results revealed that the disease-causing mechanism of BEST1 mutations is centered on the indispensable role of BESTROPHIN1 in mediating the long speculated Ca2+-dependent Cl- current in RPE, and demonstrate that the pathological potential of BEST1 mutations can be evaluated and predicted with our iPSC-based ‘disease-in-a-dish’ approach. Moreover, we demonstrated that patient RPE is rescuable with viral gene supplementation, providing a proof-of-concept for curing BEST1-associated diseases.